2021
DOI: 10.3390/cells11010083
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Monitoring of Human T Cell Responses to Skin Sensitizing Chemicals—A Systematic Review

Abstract: Background: Chemical allergies are T cell-mediated diseases that often manifest in the skin as allergic contact dermatitis (ACD). To prevent ACD on a public health scale and avoid elicitation reactions at the individual patient level, predictive and diagnostic tests, respectively, are indispensable. Currently, there is no validated in vitro T cell assay available. The main bottlenecks concern the inefficient generation of T cell epitopes and the detection of rare antigen-specific T cells. Methods: Here, we sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 147 publications
0
9
0
Order By: Relevance
“…So far, mainly interactions of chemicals with peptides presented by MHC proteins have been studied ( Aparicio-Soto et al, 2021 ). Interactions with TCR residues remain unexplored although they have been theoretically addressed as “p-i TCR” concept ( Pichler, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, mainly interactions of chemicals with peptides presented by MHC proteins have been studied ( Aparicio-Soto et al, 2021 ). Interactions with TCR residues remain unexplored although they have been theoretically addressed as “p-i TCR” concept ( Pichler, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, optimal metal salt concentrations for the in vitro distinction of allergic and non-allergic individuals have not been established. 16,67,69 Relatively high metal salt concentrations likely capture the complete reactive T cell pool but may activate T cells without in vivo relevance. So far, lower metal ion concentrations have not been associated with improved nickel allergy detection.…”
Section: F I G U R Ementioning
confidence: 99%
“…It has been reported that as many as 20% of the European population is allergic to at least one chemical. [1][2][3] ACD is characterized by delayed-type hypersensitivity (DTH) reactions, also called Type IV reactions. DTH reactions can result upon exposure to various agents.…”
Section: Introductionmentioning
confidence: 99%
“…Allergic contact dermatitis (ACD) represents an important occupational health burden. It has been reported that as many as 20% of the European population is allergic to at least one chemical 1–3 . ACD is characterized by delayed‐type hypersensitivity (DTH) reactions, also called Type IV reactions.…”
Section: Introductionmentioning
confidence: 99%